ETHICS OF COURT INTERPRETERS - NARTOWSKA, Karolina (Comparative Legilinguistics, 2013)
Complying with the rules of professional ethics during court interpreting is one of the most significant aspects of the court interpreter’s profession. Although associations of translators and interpreters draw up sets of rules in the form of professional codes, most of the practicing translators are not well acquainted with them, especially as the curricula of translation studies do not include ethics. The aim of this article is to present how the prescriptive norms of professional conduct can be applied in practice during court interpreting. The interpreters’ performance is discussed in view of their adherence to the principle of impartiality, on the example of the interpreted criminal proceedings in the Austrian court. The analysis reveals that court interpreters tend to violate this principle, by modifying the interpreted statements, lack of loyalty to the speaker, showing emotions or by assuming the role of a judge’s helper. The research further shows that the prescriptive rules are not always congruent with reality, as the ethical performance of the interpreter is often determined by the expectations of the other participants of the procedure. Due to the above, it seems vital to draw the attention of both the court interpreters and the representatives of the legal profession to the ethical aspect of court interpreting.